The Relationship between Clinical Competence and Organizational Commitment and Factors Affecting it in Nurses Working in Intensive Care Units of Kermanshah Public Hospitals in 2017 - Behrouz Bijan; Jahangir Rezaei; Hossein Ashtarian; Amir Hossein Hashemian; Hiva Azami (Hamadan University of Medical Sciences, 2024)
Background and Objective: Organizational commitment is a state in which a person considers the organization and especially its goals to be his representative and has the desire to remain a member of that organization. Clinical competence is the foundation of practical nursing work. This research was conducted with the aim of investigating the relationship between clinical competence and organizational commitment and related factors in nurses working in special departments of hospitals affiliated to Kermanshah University of Medical Sciences in 2017. Materials and Methods: In this correlational study, 227 nurses working in the special care departments of educational hospitals in Kermanshah were selected by available sampling method. The data collection tool included Allen and Mayer's questionnaire of nurses' clinical competence and organizational commitment, whose reliability and validity have been proven in various studies. Data were analyzed using SPSS version 22 software and at a significance level of P>0.05. Results: The average scores of organizational commitment and clinical competence in nurses were 119.9 ± 23.5 and 73.35 ± 2.18 respectively. No significant relationship was found between clinical competence and organizational commitment. The average score of clinical competence in nurses who had clinical work experience between 6-10 years was higher than others (P < 0.05). Conclusion: In this study, clinical competence and organizational commitment of intensive care unit nurses were high, but no significant relationship was observed. Therefore, the health service system can increase their commitment by improving the clinical qualification of nurses or employing nurses with higher qualifications.